CROSS-GENERATIONAL INCLUSIVITY OF TRADITIONAL PERFORMING ART PRESERVATION: A CASE STUDY OF LUDRUK MEDANG TARUNA BUDAYA - Adiyani, Lady Khairunnisa; Riyanto, Edi Dwi; Afdholy, Nadya (Universitas Muhammadiyah Surakarta, 2024)
This research explores the preservation of performing arts based on a cross-generational inclusivity perspective using a case study of ludruk Medang Taruna Budaya in Surabaya, Indonesia. This type of research uses a qualitative approach with a purposive sampling method with data analysis techniques using ethnography. The data for this research was collected using direct interviews, observation, and documentation from August to December 2023 in Surabaya. The results of this study show that the characteristics of cross-generational ludruk groups in the performing arts can maintain the existence of ludruk. In addition, the existence of cross-generational ludruk can also increase the interest of the younger generation in preserving ludruk performances as one of the traditional arts. The findings of this study underline the importance of the role of cross-generational collaboration in the process of preserving ludruk as a traditional performing art. This research also shows the importance of cross-generational regeneration in the preservation of traditional arts. Therefore, through this research, it can be concluded that for the values of traditional ludruk to survive, it must adjust to the specific needs of the community and keep up with the times by following cross-generational developments and making modifications.